Interactions Between Phosphorus, Zinc, and Iron Homeostasis in Nonmycorrhizal and Mycorrhizal Plants - Xie, Xianan; Hu, Wentao; Fan, Xiaoning; Chen, Hui; Tang, Ming (Frontiers in Plant Science, 2019)
Phosphorus (P), zinc (Zn) and iron (Fe) are three essential elements for plant survival, and severe deficiencies in these nutrients leads to growth retardation and crop yield reduction. This review synthesizes recent progress on how plants coordinate the acquisition and signaling of Pi, Zn and Fe from surrounding environments, and which genes are involved in these Pi-Zn-Fe interactions with the aim of better understanding of the cross-talk between these macro- and micro-nutrient homeostasis in plants. In addition, identification of genes important for interactions between Pi, Zn and/or Fe transport and signaling are useful targets for breeders for improvement in plant nutrient acquisition. Furthermore, understand these processes in arbuscular mycorrhizal plants, the preliminary examination of interactions between Pi, Zn and Fe homeostasis in some relevant crop species have been performed at the physiological level, and are summarized in this article. In conclusion, the development of integrative study of cross-talks between Pi, Zn and Fe signaling pathway in mycorrhizal plants will be essential for sustainable agriculture all around the world.